Acoustic Characteristics of Composite Structures Used in Train - Juricka, Martin; Fojtl, Ladislav; Rusnakova, Sona; Jurickova, Eva (Manufacturing Technology Journal, 2020)
This paper presents a study focused on sandwich structures as well-known train construction materials that are composed of two thin and rigid face sheets and a thick, low-density core material. For trains, the wheel-rail inter-face is the main source of noise, and the wheel-rail roughness, especially in the presence of rail corrugation, is the main excitation source transmitted to the interior and area for passengers. The purpose of the study is to optimize the acoustic properties of a composite sandwich panel used for train floors and walls. Sound absorption coefficient (?), noise reduction coefficient (NRC) and Transmission loss (TL) evaluations have been implemented and experimentally validated on a typical sandwich material used for trains. The opportunity to use a different material can be concretely calculated and modified for critical frequency ranges. Sound transmission loss levels of the structural components as the floor and wall of the train body, which are required of producers and cus-tomers, were tested in acoustic laboratory and acoustic devices according to ASTM and ISO standards. It is demonstrated that, for honeycomb and cork sandwich panels, acoustic response is not sensitive to cell size. For foam core sandwich panels, it is observed that different compositions with thin layers are effective in the fre-quency range of 50 - 1000 Hz.
Keywords: composite structures; sound absorption coefficient; noise; train; wheel rail